Marine Bacterioplankton Seasonal Succession Dynamics. Issue 6 (June 2017) - Bunse, Carina; Pinhassi, Jarone
Abstract : Bacterioplankton (bacteria and archaea) are indispensable regulators of global element cycles owing to their unique ability to decompose and remineralize dissolved organic matter. These microorganisms in surface waters worldwide exhibit pronounced seasonal succession patterns, governed by physicochemical factors (e.g., light, climate, and nutrient loading) that are determined by latitude and distance to shore. Moreover, we emphasize that the effects of large-scale factors are modulated regionally, and over shorter timespans (days to weeks), by biological interactions including molecule exchanges, viral lysis, and grazing. Thus the interplay and scaling between factors ultimately determine the success of particular bacterial populations. Spatiotemporal surveys of bacterioplankton community composition provide the necessary frame for interpreting how the distinct metabolisms encoded in the genomes of different bacteria regulate biogeochemical cycles. Trends: Seasonal succession in bacterioplankton is observed in polar, temperate, and tropical regions, and the amplitude in population dynamics often increases with distance from the equator. Intriguingly, novel sequencing methods for identifying bacterial populations allow teasing apart how key physical, chemical, and biological factors shape bacterial community composition at different spatiotemporal scales. A challenge in microbial oceanography consists of providing direct evidence for cause–effect linkages between dissolved organic matter quantity/quality and the dynamics of specific bacterioplankton.